Effectiveness of Cadaver Compared to Plastination as Anatomy Learning Media: Medical Student Perspective - Suharto, Muhammad Ilham; Hayati, Taureni; Hanifah, Hanifah; Mozart, Mozart (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Anatomy is a fundamental component of medical education, playing a pivotal role in understanding the structure and function of the human body. Cadaver-based anatomy learning remains widely used in many medical faculties; meanwhile, plastination as an alternative method, offering efficiency and practicality. This study aimed to evaluate the effectiveness of cadaver and plastination learning media in improving anatomical understanding among first-year medical students.Methods: This was a cross-sectional quantitative study with a pretest-posttest control group design conducted in November-December 2023. The study included 69 first-semester medical students from the Universitas Pertahanan, Republic of Indonesia who had not previously received musculoskeletal anatomy lectures. Participants were divided into cadaver and plastination groups. A questionnaire was distributed before and after the anatomy class. Data were analyzed with the Mann-Whitney, Wilcoxon, and paired sample t-test.Results: Both cadaver and plastination groups showed a significant increase in post-test scores (p<0.05), indicating that each method effectively improved students’ anatomical understanding. However, there was no significant difference between the two groups (p-value=0.253), suggesting comparable effectiveness between cadaveric and plastinated teaching media.Conclusions: Cadaveric and plastinated learning media are equally effective in improving anatomical knowledge among first-semester medical students. A thorough understanding of human anatomy is essential not only for clinical competency but also for advancing knowledge related to wellness, healthy aging, and the management of degenerative diseases.